EFFECTIVENESS OF PHARMACIST COUNSELING ON ADHERENCE TO ANTIHYPERTENSIVE THERAPY OF HYPERTENSION PATIENTS IN PUSKESMAS NGLETIH - Indah Yuli Antika (Strada Journal of Pharmacy, 2019)
Hypertension or high blood pressure is an increase in systolic blood pressure ≥140 mmHg or diastolic blood pressure ≥90 mmHg in two measurements with an interval of five minutes in a state of rest/quiet. The use of antihypertensive drugs must always be monitored because long-term use of drugs will affect adherence to taking medication and cause further complications or disease severity. Counseling provided by pharmacists is one of the efforts to educate and monitor patient treatment to increase patient compliance in undergoing treatment.